Students Learning Interest in the Class IX Biology Science Subject at SMP Negeri 1 Pamona Barat Poso District - Alfian*, Melky; Tjenemundan, Delfince; Allolayuk, Sertin; Ambotuo, Viskarita F.M; Junaedi, Elisabeth; Tobondo, Yuyun Alfasius (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2024)
The interest in learning at West Pamona State Middle School, especially in science subjects, can be said to be in a good category by the learning demands in the curriculum, but there are still many things that teachers still don't understand in encouraging students to develop their motivation and interest. in learning, this is because it still appears that students are not fully ready to learn and are not encouraged to think creatively in the learning process. The subjects in this research were the principal, science teacher, and class IX students at West Pamona 1 Public Middle School, Poso Regency. The results of research based on data analysis show that the description of the learning process of class IX students at SMP Negeri 1 West Pamona in encouraging interest in learning in the Biology science subject is in the medium category, namely at a percentage of 63%. The efforts made by the Biology Science teacher to encourage class IX students to develop an interest in learning at SMP Negeri 1 Pamona Barat, is by directing students to be able to generate ideas, answers, or find problems from learning material, encouraging the ability to be able to try, find solutions to problems. in the learning process, as well as utilizing learning resources such as school facilities and infrastructure. Inhibiting factors that influence class IX students in developing an interest in studying Biology Science at West Pamona 1 Middle School are factors that originate from within the students, such as not being ready to start the learning process due to disruption of physical health, excessive use of cellphones, and also conditional factors. Children's environment is not good, thus triggering juvenile delinquency.